Assessment of Soil Contamination in Area Surrounding Tuwaitha Nuclear Facilities - Ali A. Fahad Al-Taii; Shakir M. Al-Jobori; Jabbar F. Al-Maadhidi (Journal of Madenat Alelem University College, 2012)
The wide spread looting of the Tuwaitha Nuclear Facilities as well as damaging of some buildings in 2003, had offered possibilities of contamination of soil environment inside the Site. The objective of the present work was to investigate soil contamination to help in future decontamination programs. A total of 25 soil surface samples (including one reference sample) covered different locations in the Site were collected in March 2011. High purity Ge detector was used for gamma spectrometry of soil samples. Data of total and spectral gamma for U series, Th series, 40K and 137Cs are presented. Slight variations were observed in specific activity of the U series (214Bi or 214Pb and 226Ra) among measured soil samples where the range was 10.3-12.7 for 214Bi as compared with 12.2-33.4 Bq/kg for 226Ra. Values of both 214Bi and 226Ra are in the range of reference sample specific activity indicating that no evidence of contamination had occurred in the investigated area. Results of activity concentrations of thorium series (228Ac or 208Tl, 212Pb, and 212Bi) are in the range of reference sample and close to those values given worldwide for natural uranium in soil. The levels of 40K in soil are within the natural abundance of this isotope in the soil where the range was 207.6-266.1 with 220.3 Bq/kg for the reference sample. On the other hand, 137Cs specific activities showed great variation among measured samples. The minimum value for 137Cs was 0.6 and the maximum 7.6 compared with 0.8 Bq/kg for the control soil sample. The non-uniformity of radioactivity concentration of 137Cs suggest the presence of contamination in some locations although this level is considered as an acceptable level and no hazardous effect will be generated